PENGARUH PEMBERIAN REWARD TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AKIDAH AKHLAK DI MAN 2 KOTA PALU - Firdausi, Atika; Nursupiamin; Mistiani, Wiwin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the impact of reward on students’ learning motivation in Akidah Akhlak at MAN 2 Kota Palu. Low learning motivation among students has been identified as a challenge that can hinder their academic achievement and engagement in religious education. Therefore, this research aims to determine whether the implementation of reward significantly enhances students’ learning motivation. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The sample consisted of 91 students from three classes. Data were collected using a learning motivation questionnaire that had been tested for validity and reliability. The normality of the data was assessed using the Shapiro–Wilk test, and differences between pretest and posttest scores were analyzed using the Paired Samples T-Test. The findings revealed an increase in the mean learning motivation score from 29.4 in the pretest to 34.2 in the posttest. The Paired Samples T-Test indicated a significant difference with t(90) = -14.40, p < 0.001, while the effect size, measured by Cohen’s d = 1.51, demonstrated a very large effect. These results confirm that reward is an effective strategy to improve students’ learning motivation in Akidah Akhlak, suggesting that the integration of reward-based interventions can positively influence students’ engagement and performance in religious education settings.